Performance of Kaolin Clay on the concrete pavement - Putra Jaya, Ramadhansyah; Noram Irwan, Ramli; Mohd Ezree, Abdullah; M. N.A., Shahafuddin; Haryati, Yaacob; M. H., Wan Ibrahim; Mohamed Nazri, Fadzli; A. A., Mohammed (IOP Publishing, 2018)
This paper investigates the performance of concrete pavement containing kaolin clay with their engineering properties and to determine the optimum kaolin clay content. The concrete used throughout the study was designed as grade 30 MPa strength with constant water to cement ratio of 0.49. The compressive strength, flexural strength and water absorption test was conducted in this research. The concrete mix designed with kaolin clay as cement replacement comprises at 0%, 5%, 10% and 15% by the total weight of cement. The results indicate that the strength of pavement concrete decreases as the percentage of kaolin clay increases. It also shows that the water absorption increases with the percentage of cement replacement. However, 5% kaolin clay is found to be the optimum level to replace cement in a pavement concrete.